2003
DOI: 10.1046/j.1365-277x.2003.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of food portion sizes: a comparison between using descriptions of portion sizes and a photographic food atlas by children and adults

Abstract: The findings would suggest that either an alternative method or a modification of the methods used here for estimating portion sizes in young subjects, for example standard food portion sizes for children of different ages such as those that are being developed by the Food Standards Agency, would be more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
137
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 11 publications
6
137
7
1
Order By: Relevance
“…Visual aids, such as food photographs, help circumvent many of these problems and may help improve the accuracy of food portion quantification (3)(4)(5)(6)(7) . However, there is a crucial need to determine the error level induced by such an approach (8)(9)(10)(11)(12)(13) .…”
mentioning
confidence: 99%
“…Visual aids, such as food photographs, help circumvent many of these problems and may help improve the accuracy of food portion quantification (3)(4)(5)(6)(7) . However, there is a crucial need to determine the error level induced by such an approach (8)(9)(10)(11)(12)(13) .…”
mentioning
confidence: 99%
“…Lillegaard et al (9) and Frobisher and Maxwell (11) also found that there were no statistically significant differences in the identification of portion size in food photographs according to age. In the present study, the adolescents' ability to identify food portion size in the photographs was independent of food characteristics, as the identification of food portions in the photographs was similar for foods with natural portions and for amorphous foods.…”
Section: Discussionmentioning
confidence: 96%
“…The validity of photographs used in food intake assessment has been assessed among adolescents with acceptable results (7)(8)(9)(10)(11) .…”
mentioning
confidence: 99%
“…A photographic booklet is convenient compared with three-dimensional models for example, since it is easy for the interviewer to carry and can include a wide range of different types of foods. In high-income countries, the validity of using food photographs in portion size estimation has been studied in different age groups, including adults (5)(6)(7)(8)(9) , adults and elderly persons (10) and children and adolescents (7,11,12) . The study designs have varied from studies in which the subjects serve themselves a variety of foods in portions of their choice and the next day they are asked to recall the food items and estimate their amounts (5) to studies in which the food is not eaten but shown to the subject and the assessment of portion size is done simultaneously (9) .…”
mentioning
confidence: 99%
“…The study designs have varied from studies in which the subjects serve themselves a variety of foods in portions of their choice and the next day they are asked to recall the food items and estimate their amounts (5) to studies in which the food is not eaten but shown to the subject and the assessment of portion size is done simultaneously (9) . In general, despite the fact that there is large variation in individuals' ability to estimate portion sizes (7)(8)(9)(10)(11)(12) , many studies have shown acceptable results on the group level (6,(8)(9)(10)(11)(12) and the use of food photographs has become an established practice in dietary studies. More recently, portion size photographs have also been developed to be used on computer screen (12)(13)(14) .…”
mentioning
confidence: 99%